HOW TO MAP THE MEANING OF “BRINGING “ IN LIO LANGUAGE - Genua, Veronika (Lingual Journal of Language and Culture; Vol 1 No 1 (2016)DO - 10.24843/LJLC.2016.v01.i01.p09, 2016)
This study aims at describing the natural semantic metalanguage (NSM) that explain the meaning of words in detail. This paper describes the meaning of “to bring” in Lio language, as one of languages in Flores. The verb tu “to bring” explains something to be brought of head to hand. The verb tu with polysemy composition act, namely do and move to the entity part and loacted at a place on certain part of human body.
Keywords: to bring, do, polisemy,move